2020
DOI: 10.1111/dom.14211
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter‐2 inhibitors and atrial fibrillation in the cardiovascular and renal outcome trials

Abstract: Dapagliflozin is a sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor that has recently been shown to reduce the incidence of reported episodes of atrial fibrillation (AF)/atrial flutter in the DECLARE‐TIMI 58 trial. This raises the question regarding whether SGLT2 inhibitors can reduce the incidence of AF in a high‐risk population. We searched for trials comparing SGLT2 inhibitors to placebo in high‐risk individuals with or without diabetes (ie, cardiovascular and renal outcome trials) and that reported the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 33 publications
2
71
1
1
Order By: Relevance
“…Along with the results of individual randomized controlled trials (RCTs) and meta-analyses [6,7], this finding supports the suggested protective effect of SGLT2i against AF. To date, observational studies have provided conflicting results.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Along with the results of individual randomized controlled trials (RCTs) and meta-analyses [6,7], this finding supports the suggested protective effect of SGLT2i against AF. To date, observational studies have provided conflicting results.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, atrial fibrillation (AF) has been shown to occur less frequently among patients who received dapagliflozin than among those who received placebo in the DECLARE trial (HR 0.81; 95% CI 0.68-0.95) [5]. Other studies have reported similar lower rates of AF among patients randomized to SGLT2i, and two meta-analysis calculated a 21% relative risk reduction [6,7]. This finding is relevant because T2D is an established risk factor for AF [8,9], which can cause embolic stroke, precipitate HF [10], or result in hospitalization for the need of rate control.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated that SGLT2i could reduce the oxidative stress in cardiomyocytes, which in turn reverses myocardial structural/electronic remodeling (22,23). The posthoc analysis of the DECLARE-TIMI 58 trial confirmed that dapagliflozin has a lower incidence of AF over placebo, indicated the potential benefit of SGLT2i in preventing AF/AFL (24), as confirmed by subsequent meta-analyses (25,26). Recent studies have reported beneficial effects of SGLT2i in preventing atrial remodeling even in non-diabetic conditions.…”
Section: Introductionmentioning
confidence: 81%
“…In a recent meta-analysis, Li et al indicated that the AF/AFL reduction benefit of SGLT2i have no relevance with age, body weight, and systolic blood pressure at baseline (26). In another meta-analysis, Okunrintemi et al considered the AF/AFL reduction may be associated with decreased uric acid and increased magnesium induced by SGLT2i (25). Moreover, the protective effects of SGLT2i against AF/AFL may be direct actions on cardiac remodeling by reducing oxidative stress (62), which can prevent mitochondrial dysfunction and improve mitochondrial energetics (63).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of AF was numerically lower in all, and statistically lower in some clinical trials comparing SGLT2I users and controls. (16-19) A recent meta-analysis of 16 randomized controlled trials demonstrated a significant reduction of AF and atrial flutter amongst SGLT2I and placebo users. (20) Although findings from the Cardiovascular mortality and morbidity in patients with type 2 diabetes following initiation of sodium-glucose co-transporter-2 inhibitors versus other glucose-lowering drugs (CVD-REAL Nordic) study demonstrated an insignificant difference in stroke and atrial fibrillation between dapagliflozin and DPP4I users, their analysis did not adjust for clinical or biochemical confounders, nor a history of the two diseases respectively.…”
Section: Discussionmentioning
confidence: 99%